Implementing Experiential Marketing in the Digital Age for a More Sustainable Customer Relationship - Urdea, Ana-Maria; Constantin, Cristinel Petrişor; Purcaru, Ioana-Mădălina (MDPI AG, 2021)
We reviewed 58 empirical articles from the last two decades on experiential marketing in the e-commerce context. This literature review seeks to shed light into the fields of experiential and digital marketing, addressing the gaps in experiential aspects that appear during an online shopping session found in the literature. Thus, the paper identifies the elements that create the optimal consumers’ experience together with advantages, challenges, and strategic advice associated with the overall digital experience, an aspect that develops a more sustainable relationship between customers and e-businesses. The findings reveal that the most reported advantage of the overall digital experience is that it provides enhanced satisfaction, an aspect that is crucial for both consumers and online businesses, while some noted that frequent challenges are providing high levels of interactivity and trust. We found several other advantages and challenges of online consumer experience that led to the outlining of the strategic advice for online businesses, all being discussed in detail. The paper addresses a theoretical framework of digital marketing that is relevant for both academics and practitioners, suggestions for future research directions, and key research implications being offered.